Food Self-Reliance Through Self-Care of The Garden Medicinal Plants (Asman Toga) in Jerusawit Village, Karanganyar Central Java - Fithar, Adhiyatiin; Prasetyo, Anggas Tri; Devi, Anny Fitria; Maulidya, Auliya Shofi; Utami, Ayuningsih Tri; Achya, Berlian; Prasasti, Carolina Dea Wahyu; Ningtias, Cicilia Winda Prastia; Fadhila, Dian May; Prabowo, Dimas Luhur Aji; Wardhani, Puspita Indra (Journal of Community Services and Engagement: Voice of Community (VOC), 2022)
Indonesia's food consumption rises as a result of the country's rapid population expansion. To preserve food security, it is required to fulfill the community's food requirements so that the people's welfare is ensured. This article aims to find out the efforts made by the villagers of Jerukawit Karanganyar to preserve food security through the care of the garden medicinal plants (asman toga). The community of Jeruksawit Karanganyar created a group to plant toga plants on the empty area surrounding their home. There are eleven dasa wisma target groups and one core group. According to the survey's findings, market-sold plant output remains low. As a result of an ineffective marketing plan, support is still required.